Kinerja Keuangan, Ukuran Perusahaan, dan Aksi Korporasi serta Implikasinya terhadap Harga Saham Barang Konsumsi - Mustanwir Zuhri; Eva Dian Permatasari (Sekolah Pascasarjana Perbanas Jakarta, 2023)
This study objective is to analyze the impact of financial performance, firm size, and corporate action toward stock price. The analysis unit of this study is consumer goods company listed in Bursa Efek Indonesia, year 2015 – 2020. Sampling techniques developed in this research is purposive sampling. The amount of sample is 13 companies. The panel data regression is operated for analysis. The result shows current ratio has no effect on stock price, debt to equity ratio has negative impact on stock price, total asset turnover has no impact on stock price based on α of 5% but has positive impact based on α of 10%. Return on equity, perice earning ratio, and firm size have positive effect on stock price but dividend payout ratio has negative impact on stock price.